Potential effects of cinnamon on cancer prevention and progression - Anderson, Madison; Hrivnak, William; Prak, Khanneth; Stockert, Amy (Frontiers in Nutrition, 2025)
Cinnamon has been used medicinally for centuries, but recently in vitro research has suggested it may have a role in cancer prevention and potentially treatment. The search for alternative and subjunctive therapies is essential due to the public demand and the increasing cost of healthcare. Here we review the biologically active components of cinnamon and discuss the methods of potential cinnamon activity against cancer, including: transcription factor regulation and kinase activity. Nuclear Factor kappa B (NFκB) is a stress sensitive transcription factor that regulates transcription of genes involved in tumor progression and is inhibited by cinnamon components. Another way that cinnamon inhibits tumor growth is by suppression of transcription factor activator protein 1 (AP1) which interacts with genes responsible for apoptosis, metastasis and inflammation. Hypoxia-inducible transcription factor 1 (HIF1) and vascular endothelial growth factor (VEGF) are involved in angiogenesis, especially in the tumor microenvironment. The HIF1-VEGF pathway is a target of cinnamaldehyde, a compound found in cinnamon. Nuclear factor erythroid related factor 2 (Nrf2) is also examined and has been indicated to affect cancer progression and potentially provide preventative measures; various cinnamon derivatives target Nrf2. A cinnamaldehyde derivative has been implicated in a reduction of the mitogen-activated protein kinases (MAPKs), which are a group of kinases that regulate proliferation. Additionally, cinnamon components have been tied to cancer prevention by positively affecting the gut microbiome and inhibiting inflammation. The review concludes with a discussion of the future research needed, including the need for clinical studies and potential risk associated with cinnamon intake.